The Relationship Between Adult Attachment and Suicidal Thoughts and Behaviors: A Systematic Review. Issue 1 (2nd January 2021) - Zortea, Tiago C.; Gray, Cindy M.; O'Connor, Rory C.
Abstract : We aimed to (1) determine the extent of the relationship between attachment and suicidal thoughts and behaviors (STB), (2) investigate whether any gender differences exist, and (3) conduct a theoretical synthesis of the included studies. A systematic search of the databases Web of Science; EBSCO Host Medical and Psychology-related resources, which includes CINAHL, Health Source: Nursing/Academic Edition, Psychology and Behavioral Sciences Collection, and PsycINFO; and EMBASE was conducted, with 52 studies meeting the inclusion criteria. While secure attachment acts as protective factor, insecure attachment orientations appear to be vulnerability factors compromising an individual's capacity to cope with relationship issues, increasing suicide risk. There is insufficient evidence about gender differences. The theoretical synthesis suggests that attachment, interacting with other psychological traits in response to negative life events, acts as a vulnerability or protective factor for STB. Implications for treatment are also discussed.